Sustainable Competitive Advantage in Bekasi City Hospitals: The Role of Sustainable Governance, Alignment of Physician Management, and Organizational Capabilities - Waluyo Dwi Cahyono; Hapzi Ali (Dinasti International Journal of Digital Business Management, 2026)
The increasingly dynamic competition in the hospital industry requires healthcare organizations to possess a competitive advantage that is not only effective in the short term but also sustainable. Based on data from the Central Statistics Agency and the Bekasi City Health Department for the year 2026, there are 47 hospitals—comprising both public and private facilities—that compete with one another to provide the best healthcare services to the public. This scientific article is a literature review within the scope of Strategic Management. The purpose of this article is to develop hypotheses regarding the relationships among variables to be used in future research, specifically the influence of Sustainable Hospital Governance on Hospital Sustainable Competitive Advantage through Physician Management Alignment and Hospital Organizational Capability. The research data for this study were sourced from online libraries, Google Scholar, Mendeley, and various other academic resources. The research method employed library research based on e-books and open-access e-journals, using qualitative descriptive analysis. The results of this study indicate that: 1) Sustainable Hospital Governance influences Physician Management Alignment; 2) Sustainable Hospital Governance influences Hospital Organizational Capability; 3) Physician Management Alignment influences Hospital Sustainable Competitive Advantage; and 4) Hospital Organizational Capability influences Hospital Sustainable Competitive Advantage. These findings reinforce the view that the success of modern hospitals is determined not only by physical resources but also by sustainable governance, alignment between physicians and management, and organizational capability to adapt to changes in the healthcare environment.